The process of transition from pediatric to adult healthcare services for nephrological patients: Recommendations vs. reality—A single center experience - Scarponi, Dorella; Cangini, Gabriella; Pasini, Andrea; La Scola, Claudio; Mencarelli, Francesca; Bertulli, Cristina; Amabile, Domenico; Busutti, Marco; La Manna, Gaetano; Pession, Andrea (Frontiers in Pediatrics, 2022)
Transitional care is an essential step for patients with kidney disease, and it is supported by policy documents in the United Kingdom and United States. We have previously described the heterogeneous situation currently found in Europe regarding certain aspects of transitional care: the written transition plan, the educational program, the timing of transfer to adult services, the presence of a coordinator and a dedicated off-site transition clinic. In line with the transition protocol “RISE to transition”, the objective of this paper is to describe the experience of the Bologna center in defining a protocol for the management of chronic kidney disease and the difficulties encountered in implementing it. We apply this model to various chronic diseases along the process of transfer to adult services. It begins when the patient is 14 years old and is complete by the time they reach 18. The family is continuously involved and all the patients in transitional care receive continuous medical care and psychological support. We identified a series of tests designed to measure various criteria: medical condition, psychological state, quality of life, and degree of patient satisfaction, which are repeated at set intervals during the transition process. The organization of the service provided an adequate setting for taking charge of the patients in the long term. The transition program implemented by the adult and pediatric nephrology services of the Bologna center has lowered the risk of discontinuity of care and greatly improved the patients' awareness of responsibility for their own healthy lifestyle choices.